Innovation of a Project Module Based on the Ajak Temani Mandiri Learning Model Integrated with Local Wisdom to Improve the Creative Dimension of Elementary School Students - Rukmi, Dian Aprelia; Nisa, Ana Fitrotun; Zulfiati, Heri Maria (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
Creativity is one of the key dimensions in the independent curriculum. It is also a crucial skill to possess in the 21st century. This study aims to innovate a project module based on the Ajak Temani Mandiri learning model, integrated with local wisdom, to improve the creative dimension of elementary school students in a feasible and effective way. The study used Research and Development (R&D) with the Borg and Gall model, consisting of ten stages: (1) research and information collection, (2) planning, (3) developing a preliminary form of the product, (4) preliminary field testing, (5) product revision, (6) main field testing, (7) operational product revision, (8) operational field testing, (9) final product revision, and (10) dissemination and implementation. Data collection was done through interviews, observations, questionnaires, and documentation. Data analysis employed qualitative and quantitative descriptive techniques with inferential statistics. The subjects were 76 grade IV elementary school students. Results of the study showed: (1) a project module was developed, with characteristics in line with the ATM learning model. The module was integrated with local wisdom and incorporated Project-Based Learning (PBL), (2) the module was deemed